Knowledge, Attitudes, and Practices: Preventing Delayed CINV with Antiemetics - Ratih Pratiwi Sari; Muhammad Darwin Prenggono; Aditya Maulana Perdana Putra; Mahardian Rahmadi; Suharjono Suharjono (Journal of Public Health and Pharmacy, 2026)
Introduction: Chemotherapy-induced nausea and vomiting (CINV) is the most feared side effect by cancer patients. To prevent and minimize the occurrence of delayed CINV, patients are given post-chemotherapy antiemetics. Adequate patient knowledge is essential for promoting awareness of CINV and the appropriate use of post-chemotherapy antiemetics. This study examines the knowledge, attitudes, and practice of cancer patients towards the occurrence of delayed CINV and the use of post-chemotherapy antiemetics. Methods: Descriptive cross-sectional study conducted in the chemotherapy room at Hospital X, South Kalimantan, Indonesia. The study was conducted in September-November 2024. Face-to-face interviews guided by a structured questionnaire were conducted on 114 cancer patients. Results: The study revealed that patient knowledge regarding the side effects of CINV and the use of post-chemotherapy antiemetics was generally limited. Specifically, 49 respondents (43%) demonstrated a basic level of knowledge, 35 respondents (30.7%) showed sufficient knowledge, and 30 respondents (26.3%) exhibited good knowledge. Patients with higher education levels demonstrated significantly higher scores in both the attitude domain (3.31 ± 1.277) and the practice domain (3.75 ± 1.223). Conclusion: Healthcare professionals play a crucial role in educating patients on the appropriate use of antiemetic medications. Effective education aims to enhance chemotherapy patients' knowledge, attitudes, and practices regarding the use of post-chemotherapy antiemetics.